Bibliometric Review of Research on International Students in Russia - G. A. Atsyor (Высшее образование в России, 2023)
Russia is the sixth most attractive host country for international students, and this has translated into increased publications on international students in Russia. These studies have focused on the issues of Russian higher education internationalization, foreign student mobility, and acculturation challenges of international students. This paper seeks to highlight the knowledge base of international student research in Russia. Specifically, this paper represents a bibliometric review of indexed Scopus data to establish the seminal authors and current foci of research on international students in Russia. The findings indicate a present exponential growth in publications from 2015 in contrast to the slow start from 1999. The findings also demonstrate that the leading authors, with 59% of the sampled Scopus indexed articles, are affiliated with government-sponsored higher education institutions. The findings also established the most cited sources in the related literature and the current themes of research on international students in Russia. The implication of the research and limitations of the study were discussed. The directives for future research were proffered.